Advances in biomaterials for hepatic tissue engineering. (March 2020) - Kaur, Savneet; Tripathi, Dinesh M.; Venugopal, Jayarama Reddy; Ramakrishna, Seeram
Abstract: Liver/hepatocyte regeneration effectively occurs after an in vivo physiological insult and is guided by stimuli from the extracellular matrix (ECM) and signals from neighbouring cells. However, in spite of its ability to regenerate in vivo, long-term propagation of liver cells in culture has been a formidable task. This is largely because we still do not have ideal biomaterials that can recapitulate all the essential properties of a native liver ECM ex vivo . Nonetheless, many biomaterials based on natural and synthetic polymers and their blends have been developed in recent years for supporting hepatocyte cultures. Use of decellularized native liver ECM represents one vital step towards liver tissue engineering; however, native ECM has to be appropriately amended with other biomaterials. This critical review presents succinct details about the multitude of biomaterials that have been investigated over the past few years and also propose advanced options for future endeavours in hepatic tissue engineering.